STUDY OF “MAGNETIC RESONANCE IMAGING IN STROKE PATIENTS AT A TERTIARY HEALTH CARE CENTER” - RAMAMURTHY, SRI; M, DINESH; R, SOMASHEKAR; ROA, UMA MAHESHWARA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Background: One of the main causes of mortality and disability worldwide is stroke. Cerebral infarction, non-traumatic subarachnoid hemorrhage, primary intracranial hemorrhage, and various dural sinus/cerebral vein obstruction are the different types of stroke. About 80–90% of strokes are ischemic strokes, which are the most frequent form of stroke. Aim of the Study: The aim of this study was to study “Magnetic resonance imaging in stroke patients at a tertiary health care center.” Methods: This was 18-month cross-sectional research conducted in the Department of Radiodiagnosis at the Shrisatyasai Medical College and Research Institute in Chengalpattu, Tamil Nadu, from December 2020 to June 2021. Results: In the present study, middle cerebral artery is 43.3%, posterior cerebral artery (PCA) is 16.7%, anterior cerebral artery is 13.3%, lacunar infarcts is 16.7%, multiple infarcts is 8.3%, and basilar excluding PCA is 1.7% in the present study. About 73.3% of the patients (44/60) had infarcts, 10% had hemorrhage (6/60), and 16.7% had stroke mimics (10/60). Conclusion: DWI is a better imaging method than conventional MRI in detecting early ischemic lesions in stroke patients with Sensitivity of 94% and specificity of 100% was observed among acute infarct patients.